Level of financial literacy among students - I Putu Arya Mulyawan; Kompiang Martina Dinata Putri; I Dewa Ayu Agung Tantri Pramawati (Institute of Computer Science (IOCS), 2023)
Personal financial management (financial planning and control) is one form of application of financial management. For most students, college is the first time they manage their finances without the supervision of their parents. Students must be able to manage their finances properly independently and must also be able to take responsibility for the decisions they have made. This research aims to determine students' literacy levels and personal opinions about their respective financial decisions. The method used is descriptive qualitative, adjusting opinions between researchers and informants. The data source in descriptive qualitative research is a questionnaire (list of questions). The object of this research is students currently studying at the Indoneisa Institute of Business and Technology (INSTIKI) in Denpasar, Bali. The respondents in this study were 100 people. The results indicated that financial education and financial literacy should be provided early. The conclusion of this study states that the level of financial literacy possessed by students who are respondents in this study is at an intermediate level. And in deciding their respective finances, they have been able to recognize existing financial products but have not explored the procedures and processes for running them in the future.